Hubungan Self Efficacy dengan Perilaku Prokrastinasi Akademik di SMA Negeri 3 Pemalang - Sari, Rima Novita; Handayani, Arri; Mujiono (Melati Institute, 2024)
Self-confidence is also known as Self efficacy, which means a person's belief in their ability to exercise a form of control over their own functioning and events in the environment. Low self efficacy in students can make students engage in procrastination behavior, this is the basis for this study. The purpose of this study was to determine whether there is a relationship between self afficacy and students' academic procrastination behavior. In this study, the method used was quantitative with the type of correlation research, the population in this study was 360 students. The sample of this study took 20% of the population so that the sample used was 72 students determined by cluster random sampling technique. Based on the Pearson product moment correlation test, the calculated r value is 0.694, while the r table for a sample size of 72 is 0.229. Therefore, 0.694> 0.229, it can be concluded that there is a significant relationship between self efficacy and academic procrastination behavior in SMA Negeri 3 Pemalang. The positive relationship means that if self efficacy is high then academic procrastination behavior is low and vice versa if self efficacy is low then academic procrastination behavior is high.